The Effect of a Pro-Breastfeeding and Healthy Complementary Feeding Intervention Targeting Adolescent Mothers and Grandmothers on Growth and Prevalence of Overweight of Preschool Children. - Renata Schwartz; Álvaro Vigo; Luciana Dias de Oliveira; Elsa Regina Justo Giugliani (PLoS ONE, 2015)
The pattern and duration of breastfeeding (BF) and the age at onset of complementary feeding, as well as its quality, have been associated with the prevalence of overweight in childhood.To assess the effect of a pro-BF and healthy complementary feeding intervention, targeted to adolescent mothers and maternal grandmothers, on growth and prevalence of overweight and obesity in children at preschool age. This intervention had a positive impact on duration of BF and timing of onset of complementary feeding.This randomized clinical trial involved 323 adolescent mothers, their infants, and the infants' maternal grandmothers, when they cohabited. Mothers and grandmothers in the intervention group received counseling sessions on BF and healthy complementary feeding at the maternity ward and at home (7, 15, 30, 60, and 120 days after delivery). When children were aged 4 to 7 years, they underwent anthropometric assessment and collection of data on dietary habits. Multivariable Poisson regression with robust estimation was used for analysis.BMI-for-age and height-for-age were similar in the intervention and control groups, as was the prevalence of overweight (39% vs. 31% respectively; p=0.318). There were no significant between-group differences in dietary habits.Although the intervention prolonged the duration of exclusive BF and delayed the onset of complementary feeding, it had no impact on growth or prevalence of overweight at age 4 to 7 years.ClinicalTrials.gov NCT00910377.